Turnover of protein-bound serine phosphate in respiring slices of guinea-pig cerebral cortex. Effects of putative transmitters, tetrodotoxin and other agents - Reddington, Martin (1973)
1. The effect of various agents on the turnover of protein-bound phosphorus in respiring slices of cerebral cortex was studied. 2. Confirming previous work turnover was increased by the application of electrical pulses for 10s to the tissue. 3. Turnover was also increased by exposure of the slices for 10min to noradrenaline (0.5mm), 5-hydroxytryptamine (1μm) and histamine (0.1mm). 4. When slices were stimulated by electrical pulses in the presence of histamine the increase in turnover was the sum of the responses given by each agent above, suggesting that different phosphorylating systems were involved. 5. Tetrodotoxin (0.5μm) blocked the increased turnover due to electrical pulses, but not that due to histamine. Tetrodotoxin also prevented the increase in tissue cyclic AMP content caused by the application of electrical pulses. 6. Phosphoprotein turnover was not affected by adenosine, despite the increase in tissue cyclic AMP content given by this agent. 7. Adenosine blocked the phosphoprotein response to histamine, but did not affect the response to electrical pulses. 8. The results are discussed in relation to the hypothesis that the stimulation of protein phosphorus turnover by electrical pulses is secondary to the release of cyclic AMP in the tissue.